Circulating cKIT and PDGFRA DNA indicates disease activity in Gastrointestinal Stromal Tumor (GIST). Issue 8 (29th April 2019) - Jilg, Stefanie; Rassner, Michael; Maier, Jacqueline; Waldeck, Silvia; Kehl, Victoria; Follo, Marie; Philipp, Ulrike; Sauter, Andreas; Specht, Katja; Mitschke, Jan; Lange, Thoralf; Bauer, Sebastian; et al.
Abstract : This prospective trial aimed to investigate whether tumor‐specific cKIT and PDGFRA mutations can be detected and quantified in circulating tumor (ct)DNA in patients with active GIST, and whether detection indicates disease activity. We included 25 patients with active disease and cKIT or PDGFRA mutations detected in tissue. Mutant ctDNA was detected in the peripheral blood plasma using allele‐specific ligation (L‐)PCR and droplet digital (d)PCR. CtDNA harboring tumor‐specific cKIT or PDGFRA mutations was detected at least once in 16 out of 25 patients using L‐PCR (64%) and in 20 out of 25 patients with dPCR (80%). Using dPCR, the absolute numbers of ctDNA fragments (DNA copies/ml) and the mutant allele frequency (MAF; in percent of wild‐type control) strongly correlated with tumor size expressed as RECIST1.1 sum of diameter (SOD) in mm (ρ = 0.3719 and 0.408, respectively, p < 0.0001) and response status (ρ = 0.3939 and 0.392, respectively, p < 0.0001 and p < 0.001). Specificity of dPCR for detection of progression was 79.2% with a sensitivity of 55.2% and dPCR discriminated CR from active disease with a specificity of 96% and s sensitivity of 44.7%. With L‐PCR, correlations of MAF with tumor size and response status were less prominent. Serial ctDNA measurement reflected individual disease courses over time. Targeted panel sequencing of four patients detected additional driver mutations in all cases and secondary resistance mutations in two cases. Thus, ctDNA indicates disease activity in patients with GIST and should be incorporated as companion biomarker in future prospective trials. Abstract : What's new? For Gastrointestinal Stromal Tumors (GIST), early detection of relapsed or progressive disease is mandatory to provide adequate surgical procedures or switch medication in case of drug resistance. However, until now monitoring of GIST patients has been restricted to imaging with technical limits in sensitivity and specificity, calling for biomarkers to be developed. In this prospective trial, the authors demonstrate that in GIST patients, the amount of circulating tumor (ct)DNA harboring tumor‐specific cKIT and PDGFRA mutations correlates with disease activity and tumor size. Thus, analysis of ctDNA might complement standard imaging techniques for monitoring and follow‐up in GIST.